Forming the Anti-Bullying Character of Santri: The Role of Transformation of Adab Values from the Book of Ta’limul Muta’allim - Achmad Nurjadid Akmal; M. Bustanul Ulum (Al-Qalam Institue, 2025)
The phenomenon of bullying in educational institutions, including Islamic boarding schools, continues to be a serious challenge that threatens the integrity and welfare of students. This study aims to analyze in depth the specific contribution of the adab values taught in the Book of Ta'limul Muta'allim to the formation of anti-bullying character in students of the Nuris Salafiyyah Islamic Boarding School. Using a qualitative approach with a case study design, this study collected data through in-depth interviews with ustadz and students, as well as documentation analysis. The data was then analyzed thematically. Key findings suggest that manners toward teachers, which encompass respect and obedience, foster humility and empathy. Additionally, the practice of ukhuwah and solidarity among students, as manifested in loving and supporting one another, fosters a strong communal environment. The ability to maintain verbal communication and manage emotions also plays a crucial role in equipping students with wise communication skills, minimizing triggers of conflict and verbal aggression. These findings enrich socio-cultural theories by providing empirical evidence on the role of religious values-based environments in fostering prosocial behavior. The implication is that strengthening comprehensive adab education in pesantren can be an effective strategy to create a safe, harmonious, and value-centered learning environment, thereby significantly reducing the emergence of bullying behavior and supporting the development of positive character in students.